Chemical composition and fumigant toxicity of the essential oils from 16 species of Eucalyptus against Haematobia irritans (Diptera: Muscidae) adults - Juan, Laura Wilma (2011)
Oils extracted from various species of Eucalyptus (Eucalyptus badjensis Beuzev & Welch, Eucalyptus badjensis × Eucalyptus nitens, Eucalyptus benthamii variety dorrigoensis Maiden & Cambage, Eucalyptus botryoides Smith, Eucalyptus dalrympleana Maiden, Eucalyptus fastigata Deane & Maiden, Eucalyptus nobilis L.A.S. Johnson & K. D. Hill, Eucalyptus polybractea R. Baker, Eucalyptus radiata ssp. radiata Sieber ex Spreng, Eucalyptus resinifera Smith, Eucalyptus robertsonii Blakely, Eucalyptus rubida Deane & Maiden, Eucalyptus smithii R. Baker, Eucalyptus elata Dehnh, Eucalyptus fraxinoides Deane & Maiden, E. obliqua L'Hér) were obtained by hydrodistillation. The chemical composition of essential oils was determined by gas chromatography coupled to mass spectrometry. Essential oils were mainly composed of 1,8-cineole, α-pinene, α-terpineol, 4-terpineol, and p-cymene. Vapors from these essential oils and their major components were found to be toxic to Haematobia irritans (L.) (Diptera: Muscidae) adults. An aliquot of each oil was placed in a cylindrical test chamber, and the number of knocked down flies was recorded as a function of time. Knockdown time 50% was then calculated. Results showed that essential oil of E. polybractea had the highest knockdown activity of 3.44 min. A correlation was observed between the content of 1,8-cineole in the Eucalyptus essential oils and the corresponding toxic effect.